Effect of Capital Adequacy on Operational Efficiency of Commercial Banks in Kenya - Wanjagi, Jedidah; Nasieku, Tabitha; Fatoki, Olanrewaju (European Scientific Journal, ESJ, 2024)
This study investigates the impact of capital adequacy on the operational efficiency of Kenyan banks, highlighting its importance for financial stability and risk management using a two-step analytical approach: first, Stochastic Frontier Analysis was used to determine operational efficiency scores for each bank; second, a panel Generalized Method of Moments (GMM) regression model assessed the relationship between these scores and capital adequacy. The study employed a panel GMM Method, accounting for individual and time-specific effects as well as endogeneity and correlation biases. The study concentrated on data from 2008 to 2022, spanning a period of 14 years of data. Data was collected from verified audited financial statements from the Central Bank of Kenya and the respective banks websites. The study revealed a positive relationship between capital adequacy and operational efficiency. Specifically, an increase in capital adequacy was associated with a 10.32% improvement in operational efficiency. The study also found that market structure plays a significant role in this relationship. Based on these findings, policymakers are recommended to adopt comprehensive strategies focusing on stringent capital adequacy regulations to enhance bank performance and stability.